2011
DOI: 10.1002/sim.4305
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring binary outcomes using risk‐adjusted charts: a comparative study

Abstract: Monitoring binary outcomes when evaluating health care performance has recently become common. Classical statistical methodologies such as cumulative sum (CUSUM) charts have been refined and used for this purpose. For instance, the risk-adjusted CUSUM chart (RA-CUSUM) for monitoring binary outcomes was proposed for monitoring 30-day mortality following cardiac surgery. The RA-CUSUM inherits optimality properties of the original CUSUM charts in the sense of signaling early when there is change. However, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…In our current simulation study we included RACUSUM to show what would happen if users chose that method instead of our tests. Note that the dependence structure is not accommodated in RACUSUM or in Gombay, Hussein, & Steiner (), so this is a new feature of this study. Furthermore, Kulldorff et al () demonstrated that the performance of the CUSUM test is very sensitive to the choice of the alternative parameter value.…”
Section: Conclusion and Comparisonsmentioning
confidence: 90%
See 3 more Smart Citations
“…In our current simulation study we included RACUSUM to show what would happen if users chose that method instead of our tests. Note that the dependence structure is not accommodated in RACUSUM or in Gombay, Hussein, & Steiner (), so this is a new feature of this study. Furthermore, Kulldorff et al () demonstrated that the performance of the CUSUM test is very sensitive to the choice of the alternative parameter value.…”
Section: Conclusion and Comparisonsmentioning
confidence: 90%
“…We therefore set a horizon (a maximal sample n ) by which, if H0 has not been rejected, the surveillance procedure will be re‐started. This makes our surveillance procedure a truncated one, thus providing better control over the probability of false alarms as in Gombay, Hussein, & Steiner (). The choice of n is beyond the scope of the current study, but it is related to the same choice in group sequential tests where it has been extensively studied.…”
Section: Model and Surveillance Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that the approach of Gombay et al . is different from ours in the sense that they control the overall probability of a false alarm for a specified number of patients. We instead assume an ongoing monitoring scenario.…”
Section: Introductionmentioning
confidence: 87%